A study of the temperature effect on photoluminescence of the P3HT/MWNT nanocomposites. (2021) - Bakour, Anass; Bajjou, Omar; Baitoul, Mimouna; Massuyeau, Florian; Wéry, Jany; Maaza, Malik; Faulques, Eric
Abstract: In spite of the strong competition from recently developed nanomaterials such as graphene, carbon nanotubes continue to be promising materials for photovoltaic applications thanks to their structural advantages and cheap prices of synthesis especially the multi-walled carbon nanotubes (MWNT). Mixing of MWNT with a semiconducting polymer such as the P3HT leads to a composite material characterized with enhanced mechanical, thermal and optical properties. In order to investigate the impact of the insertion of different wt% of MWNTs on the luminescence properties of the P3HT we conducted a series of measurements by means of steady state PL and time transient PL for different samples, as well as the study of the temperature effect on these properties. The results obtained confirm the luminescence quenching effect played by the MWNTs, and prove that the lifetime of photo-generated excitons in the P3HT matrix undergoes a modification after the insertion of the MWNTs which means that a charge separation process takes place at the P3HT/MWNT interface.